The symptoms of patients with CKD stage 5 managed without dialysis. (October 2015) - Brennan, Frank; Collett, Gemma; Josland, Elizabeth A.; Brown, Mark A.
<x content-type="archive" xml:space="preserve">Abstract</x> Background There is an increasing number of patients with stage 5 chronic kidney disease (CKD) being managed conservatively without dialysis. A critical aspect of their care is symptom management. To date there is only a small body of literature examining the prevalence and severity of the symptoms they experience. Aims To describe symptom prevalence, severity and total symptom burden on patients with stage 5 CKD being managed conservatively. Methods Symptom data were collected from all the patients with stage 5 CKD being managed conservatively at their first presentation to a renal supportive care clinic. Symptoms were assessed using the patient-completed palliative care outcome scale-symptoms (POS-S) (renal) instrument, a validated symptom inventory tool for patients with CKD. Results Symptoms were evaluated in 42 patients. Their mean age was 83 years (SD: ±8.17) and the mean estimated glomerular filtration rate (eGFR) was 10.6 mL/min/1.73 m2 (SD: ±2.23). Symptoms reported by more than one-third of patients were lack of energy, 88% (CI: 78–98); difficulty with mobility, 76% (CI: 63–89); pruritus, 69% (CI: 55–83); lack of appetite, 62% (CI: 47–77); shortness of breath, 60% (CI: 45–75); drowsiness, 57% (CI: 42–72); sleep disturbance, 57% (CI: 42–72); feeling depressed, 52% (CI: 37–67); pain, 45% (CI: 30–60); constipation, 43% (CI: 28–58); feeling anxious, 43% (CI: 28–58); and skin changes, 38% (CI: 23–53). The mean number of symptoms reported on POS-S (renal) per patient was 8.1 (SD: ±3.99) of a maximum 17. Those symptoms which were most likely to be reported as 'moderate' to 'overwhelming' were fatigue (66%), difficulty with mobility (64%), pruritus (45%), disturbed sleep (45%), anorexia (43%), drowsiness (38%), depression (38%), and dyspnoea (36%). The three most prevalent symptoms were also the most severe. There was no statistical correlation between the severity of disease as measured by eGFR, haemoglobin (Hb), and prevalence or severity of symptoms. Although 92% of the studied group had a 'very high co-morbidity' index according to the modified Charlson co-morbidity index, there was no statistical correlation between the eGFR and the burden of co-morbidities nor between the burden of co-morbidities and the number or severity of reported symptoms. Conclusion Patients with end-stage kidney disease managed conservatively are burdened with multiple symptoms. Many of those symptoms are moderate to overwhelming in severity and not easily predicted on the basis of the eGFR. The responsibility for the management of these symptoms rests on all disciplines who care for this cohort of patients throughout the course of their illness.